2018
DOI: 10.1002/asia.201800017
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Supramolecular Gels and Catalysis

Abstract: Over the past two decades, supramolecular gels have attracted significant attention from scientists in diverse research fields and have been extensively developed. This review mainly focuses on the significant achievements in supramolecular gels and catalysis. First, by incorporating diverse catalytic sites and active organic functional groups into gelator molecules, supramolecular gels have been considered as a novel matrix for catalysis. In addition, these rationally designed supramolecular gels also provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 149 publications
(228 reference statements)
0
86
0
1
Order By: Relevance
“…Gels have great potential in catalysis as a result of their solvated nature and the ability of small-molecule reagents to diffuse through them-indeed, gels can be considered intermediate between homogeneous and heterogeneous catalytic systems, combining the advantages of both. [24] We recently reported that DBS-CONHNH 2 hydrogels achieve efficient in-situ reduction of precious metals to yield gels with embedded metal nanoparticles (NPs). [20c] Furthermore, gels with embedded palladium nanoparticles (PdNPs) can catalyse Suzuki-Miyaura cross-coupling reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Gels have great potential in catalysis as a result of their solvated nature and the ability of small-molecule reagents to diffuse through them-indeed, gels can be considered intermediate between homogeneous and heterogeneous catalytic systems, combining the advantages of both. [24] We recently reported that DBS-CONHNH 2 hydrogels achieve efficient in-situ reduction of precious metals to yield gels with embedded metal nanoparticles (NPs). [20c] Furthermore, gels with embedded palladium nanoparticles (PdNPs) can catalyse Suzuki-Miyaura cross-coupling reactions.…”
Section: Resultsmentioning
confidence: 99%
“…For the sake of clarity, only some selected typical examples are reported in this section to highlight the various possibilities to obtain catalytic transformations using supramolecular gels. For complementary information on this topic, we advise the reader to refer to the very recent review of Tu and coworkers [191].…”
Section: Supramolecular Physical Gelsmentioning
confidence: 99%
“…Due to the application prospects in various fields, such as chemical sensors, biocompatible materials, catalysis, drug delivery, electronics, flexible optics, templates for molecule synthesis, information storage, stimuli‐responsive materials, etc., supramolecular gel has gained more and more research interest acting as an intelligent “soft material.” 1‐4 Usually the non‐covalent interactions, including hydrogen bond, hydrophilicity/hydrophobicity, π‐π stacking, electrostatic interaction, Van der Waals force, metal‐coordination and so on, among small molecule building blocks play an essential role in the fabrication process of supramolecular gels 5,6 . The delicate cooperativity of these non‐covalent interactions as well as the contribution from solvents would generate different nanostructures with diverse morphologies and sizes, making the supramolecular gel an ideal platform for nanostructure construction and function extension.…”
Section: Introductionmentioning
confidence: 99%